Performance of bean (Phaseolus vulgaris L.) genotypes in the second-season under high and low technology management in Parana, Brazil (2017)
In the face of bean (Phaseolus vulgaris L.) crops with low grain yield in Brazil, specifically in the state of Parana-Brazil, this research aimed to evaluate the agronomical performance of different genotypes grown in the second-season under high and low technology management. The experimental design was a randomized block design with three replications in a 3x13x2 triple factorial arrangement, where Factor A was composed of three years of cultivation (second-season 12/13, 13/14 and 14/15), Factor B consisted of 13 bean cultivars (BRS Campeiro; BRS Esplendor; IPR Gralha; IPR Tuiuiú; IPR Uirapuru; BRS Ametista; BRS Estilo; BRS Notável; BRS Pérola; IPR 81; IPR Campos Gerais; IPR Curió and IPR Tangará) and Factor C consisted of 2 levels of technological management (high and low technology). The use of high-technology management resulted in higher grain yield, statistically different from the low-technology management in the second-season 12/13, 13/14 and 14/15 and from the overall mean of the three years of cultivation. Thus, greater investment in technology increases the probability of increasing in economic profitability of the producer due to the growth in bean crop productivity. The cultivar BRS Pérola exhibited grain yield values statistically higher than cultivars IPR Tuiuiú, IPR Gralha, IPR Campos Gerais, IPR Tangará, IPR Uirapuru, IPR 81 and IPR Curió, proving to be a good choice to achieve high productivity.